2015
DOI: 10.1091/mbc.e15-01-0034
|View full text |Cite
|
Sign up to set email alerts
|

PDI reductase acts onAkitamutant proinsulin to initiate retrotranslocation along the Hrd1/Sel1L-p97 axis

Abstract: Protein disulfide isomerase acts as a reductase to reduce a mutant proinsulin called Akita, priming it for retrotranslocation across the endoplasmic reticulum (ER) membrane by using the Sel1L-Hrd1-p97 ER-associated degradation machinery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 46 publications
1
46
0
Order By: Relevance
“…The notion that rather than prevent, the formation of proAVP aggregates or polymers. Given our own data and the current literature (3,33,56), we propose 2 possible modes of action for PDI in the context of proAVP ERAD, as illustrated in Figure 9C. PDI may act to reduce and unfold proAVP targeted for ERAD, which may result in the generation of unfolded substrates with highly reactive cysteine thiols.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The notion that rather than prevent, the formation of proAVP aggregates or polymers. Given our own data and the current literature (3,33,56), we propose 2 possible modes of action for PDI in the context of proAVP ERAD, as illustrated in Figure 9C. PDI may act to reduce and unfold proAVP targeted for ERAD, which may result in the generation of unfolded substrates with highly reactive cysteine thiols.…”
Section: Discussionmentioning
confidence: 82%
“…Studies have suggested that PDI subserves a pro-folding role in WT cells (30,55), and more recently, studies have demonstrated that PDI, but not other members of the PDI family (ERp57 and ERdj5), may also participate in ERAD by feeding reduced protein substrates (e.g., Akita proinsulin and thyroglobulin) to the ERAD machinery (3,33,56 (20). Single-guide RNA (sgRNA) oligonucleotides were designed for human HRD1 (5′-GGA-CAAAGGCCTGGATGTAC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the ERAD in cellular health cannot be understated, since multiple human diseases are linked to ERAD failure (Qi et al, 2017). In Akita cells, the ERAD participates in the turnover of mutant C 96 Y proinsulin in the ER, but is not sufficiently activated to prevent apoptosis (He et al, 2015). We show that CE promote ERAD activation by stabilizing its main effector, the E3 ubiquitin ligase HRD1, which accelerates the ubiquitination and proteasomal degradation of misfolded C 96 Y proinsulin.…”
Section: Discussionmentioning
confidence: 99%
“…One such process is called ER-associated degradation (ERAD), in which misfolded ER clients are retrotranslocated to the cytosol, where they are degraded by proteasomes (810). Recently, our laboratory and others identified several components of the ERAD machinery that facilitate degradation of Akita proinsulin (11), including the ER membrane-bound E3 ubiquitin ligase Hrd1, its membrane-binding partner Sel1L, and the cytosolic AAA+ ATPase p97 (12). We also reported that the ER luminal protein disulfide isomerase (PDI) may participate in reducing disulfide bonds that can help to liberate Akita proinsulin from high-MW protein complexes, generating smaller dimeric/trimeric species that are competent for retrotranslocation (12); another PDI family member, PDIA6 (encoding the P5 protein), may also play a role in this process (13).…”
Section: Introductionmentioning
confidence: 99%